Quantified Hypoxia and Anoxia in Lakes and Reservoirs - Gertrud K. Nürnberg (The Scientific World Journal)
Hypoxia and anoxia occur frequently in freshwater systems and have biological and chemical implications. Anoxia can be expressed and quantified as the anoxic factor; hypoxia, for a specific level of oxygen depletion, can be expressed as the hypoxic factor in lakes, reservoirs, and river sections. These methods summarize information of individual dissolved oxygen profiles as annual values or factors that facilitate comparison between and within lakes. Therefore, these factors are useful in the formulation and testing of hypotheses related to the dissolved oxygen status in water bodies. Methods of calculating different factors for different oxygen levels and water layers, including those applying separately to the epilimnion and hypolimnion, are presented in detail. Proven and potential applicability include: (1) the quantification of relationships with lake water quality variables and lake classification (trophic state), (2) the evaluation of restoration techniques with respect to their effects on hypolimnetic oxygen depletion, (3) the determination of internal phosphorus loading in stratified and polymictic lakes, (4) the exploration of habitat constraints due to hypoxia (e.g., fish species richness and winterkill), (5) forecasting potential effects of climatic change on oxygen content and internal phosphorus loading, and (6) the establishment and examination of criteria and guidelines with respect to hypoxia by custom-made definitions.